The first food bank in ecuador created by teachers of the Escuela Politécnica Nacional - Salguero, Yadira; Guevara, Alicia (mktDESCUBRE, 2019)
One third of all the food produced in the world is wasted, while 821 million people suffer from hunger in the world. Ecuador is on the list of Latin American countries that waste the most food, and this absurd waste occurs despite the fact that 24.5 % of Ecuadorians live in conditions of poverty, extreme poverty and indigence. As part of the solution to this social problem, at the initiative of professors of the National Polytechnic School, the first Food Bank of Ecuador was created in Quito 16 years ago. Thanks to the determined and constant collaboration of professors, students and members of the community who act as volunteers, the Food Bank fulfills its objective of avoiding the waste of food, generating concrete actions to fight hunger in the Ecuadorian capital. The Food Bank collects and selects foods received in donation, which are in optimal conditions, but which have reached the end of the marketing cycle and are generally wasted. The recovered food is distributed among people in situations of food vulnerability who are located in sectors with high poverty rates. The linkage model with the society that the National Polytechnic School carries out through the Food Bank has allowed up to date to recover more than 1.7 million kilograms of food equivalent to more than 4 million rations. The food recovered in 2018 was distributed to 13413 people from the most deprived sectors of the city, which belong to 77 institutions and 655 low-income families. The Food Bank is currently one of the largest entailment programs currently maintained by the university and which seeks to be replicated throughout the country.